Klebsiella pneumoniae liver abscess with purulent meningitis and endogenous endophthalmitis: A case report - Li, Fang; Zheng, Wenfei; Yu, Jian; Zhao, Linyan (Frontiers in Surgery, 2022)
This is a rare but typical case of a Klebsiella pneumoniae liver abscess with migratory infections including purulent meningitis and endogenous endophthalmitis. The patient had a chief complaint of 7 days of fever, 4 days of blurry vision, and 4 h of glossolalia. Ultrasound scan and computed tomography (CT) suggested a liver abscess. Both blood and drainage fluid cultures grew K. pneumoniae with a high mucosal phenotype. The patient was finally diagnosed with a K. pneumoniae liver abscess, purulent meningitis, and endogenous K. pneumoniae endophthalmitis in the right eye. Ultrasound-guided percutaneous catheter drainage (PCD) of the liver abscess was performed, and meropenem was used to control infection. The patient was given 0.1 ml of vancomycin (10 g/L) and 0.1 ml of ceftazidime (20 g/L) were by intravitreal injection for the treatment of endophthalmitis. The infection was gradually controlled after such treatments. The patient was discharged from our hospital with an improved condition. However, during the time of follow-up, she developed complications due to severe pneumonia and eventually died in a local hospital. This case revealed that a rapid diagnosis followed by appropriate treatment would improve prognosis and prevent severe metastatic complications.